تميز المرأة المسلمة وإبداعها في ضوء السنة النبوية : دراسة تاريخية - هديل، طه حسين عوض أحمد (جامعة القصيم, 2014)
يتناول هذا البحث "تميز المرأة المسلمة وإبداعها في ضوء السنة النبوية دراسة تاريخية" ظاهرة اشتهر بها عصر النبوة ، وانفرد لها المسلمون الأوائل في كثير من نواحي حياتهم الخاصة والعامة ، ألا وهي ظاهرة التميز والإبداع ، التي انتشرت بين الكثير من أفراد المجتمع المسلم لاسيما النساء اللاتي تؤكد لنا السنة النبوية أنه كان لهن من الأفعال ما يؤكد قدرتهن على الإبداع في الكثير من الأعمال التي نافسن بها الرجال في ذلك العصر، ومن الملاحظ أنه كان للتربية الصحيحة التي اتبعها النبي صلي الله عليه وسلم وتشجيعه لمن حوله من النساء الدور الكبير في تهيئة المبدعات منهن ، ممن وجدن في هذا التشجيع النبوي فرصة لإظهار ما بهن من طاقات تفجرت في الميادين التي شاركن فيها، وحققن من خلالها نجاحاتهن الباهرة . لقد توصلنا من خلال دراستنا هذه إلى أن عصر النبوة كان عصر التميز بكل مقاييسه، وأنه كان للطرق والأساليب التي أتبعها النبي صلي الله عليه وسلم مع صحابته من الرجال والنساء دور في بروز كوكبة منهم ، اشتهرت بإبداعها في كثير من الأعمال ، التي لو تعرفنا عليها، وتعاملنا معها اليوم مع أولادنا وأسرنا، وفي حياتنا الخاصة ومدارسنا لحصلنا على جيل متميز ومبدع بكل ما تعنيه الكلمة من معنا، كما كان جيل عصر النبوة، وهو ما سوف نتناوله في دراستنا هذه. Deals with a well known phenomena in the prophet period and specialized with the first Muslims in the various aspects of their private and public lives .This phenomena is the distinction and the creation which spread widely between a lot of the Islamic society members especially among the women . This is vertified by the evidences derived from the prophetic sina in which the women were known by their creative deeds in various aspects where they proved their abilities to compete even the men during that period. Moreover, it was noticed that the well education and bringing up of our prophet Mohammed peace be upon him to motivate women who were surrounded him played a significant role in preparing the creative women among them .This prophetic motivation was considered as an opportunity to show and present their capabilities in the various fields that they were participated in. From this research .it is concluded that. the prophetic period is standardized as being the distinction period .The ways and the principles that our prophet peace be upon him used with his male and female followers played a great role in presenting a sample famed by their creative deeds that if we really know them , use them in our dealings with our sons , daughters families , personal life in our teaching at schools , it will provide us with creative distinct generation exactly similar to the prophetic generation and this is what the rest of the research is going to high light on.
Keywords: المرأة المسلمة -- التاريخ الإسلامي -- السنة النبوية -- التميز و الإبداع -- تنمية المهارات